Effectiveness of carbamide peroxide and sodium perborate in non-vital discolored teeth (Journal of Applied Oral Science, 2009)
OBJECTIVE: To evaluate the efficacy of 16% carbamide peroxide gel (CP16%), tetrahydrate sodium perborate (SP) and mixture (CP16% + SP), in walking bleaching of non-vital discolored teeth. MATERIALS AND METHODS: Sixty single-rooted human premolars with intact crowns were used and initial color was assessed using Vita shade guide and standardized photos. The teeth were stained using rabbit fresh blood for 18 days and photos of discolored teeth and color evaluation were performed. The teeth were divided into 4 groups (n= 15), according to bleaching agent used: G1) CP16% gel; G2) CP16% gel + SP; G3) SP + distilled water; G4: control. The bleaching agents were replaced twice at 7-day intervals for 21 days. All teeth were evaluated by two endodontists at days 0, 7, 14 and 21 and the color changes were assessed using Vita shade guide and standardized photos. The results were analyzed by Kruskal-Wallis and Dunn's tests (p=0.05). RESULTS: The experimental groups presented statistically similar bleaching results (p>;0.05) at the end of 7, 14 and 21 days. These groups presented significantly higher bleaching efficacy than control group (G4) (p